A CLINICAL CASE OF DELIVERY OF A PATIENT WITH HEREDITARY ANGIOEDEMA - Виталий Сергеевич Самоделкин; Василий Николаевич Паличев; Елена Валентиновна Гришкевич; Наталья Владимировна Артымук; Вадим Гельевич Мозес (The Publishing House Medicine and Enlightenment, 2020)
The article presents a clinical case of delivery of a patient with orphan disease - hereditary angioedema. The complexity of managing a patient with this pathology is demonstrated.